Propuesta de un diseño administrativo y organizativo para la empresa Rafael Corredor Vargas con establecimiento de comercio Tecnieléctricos en la ciudad de Villavicencio (2021)
Currently, regardless of the type of company, there is a great difference in the role and importance of the worker for companies, however, there are still inconsistencies in the human resources area. In this sense, the problem in the Rafael Corredor Vargas company with a Tecniellecticos business establishment in the city of Villavicencio is such that at first glance it can be seen that the lack of organization has caused employees to become in a certain way conformist people who lose ideals and put limitations on their development inside and outside the organization, which leads to not improving their quality of life and those of their families, in addition to poor performance in their work. For this reason, this research proposes the development of an administrative and organizational design for said company.